Addition of peritonectomy to gastrectomy can predict good prognosis of gastric adenocarcinoma patients with intraoperatively proven single P1/P2 carcinomatosis - Sen Li; Xiuwen Lan; Hongyu Gao; Wenpeng Wang; Li Chen; Shubin Song; Yingwei Xue (Tumor Biology, 2017)
This study was to evaluate the prognosis of peritonectomy following gastrectomy for gastric adenocarcinoma patients with intraoperatively proven single P1/P2 carcinomatosis and to define the best therapeutic strategy of the patient cohort. The patients with intraoperatively proven single P1/P2 carcinomatosis from a prospectively maintained database were divided into resection group and non-resection group based on complete gross resection of peritoneal carcinomatosis. From 2005 to 2012, there were 103 patients in the resection group and 122 patients in the non-resection group. There was no difference in morbidity and mortality between groups. The patients did not have improved median survival in P1 carcinomatosis compared to P2 carcinomatosis (15.53 vs 14.80 months, p  = 0.450). The median survival was significantly improved in the resection group compared to the patients in the non-resection group (21.07 vs 13.37 months, p  < 0.001). The patients undergoing complete gross peritonectomy plus postoperative chemotherapy had a significantly longer median survival than patients who had complete gross peritonectomy alone, patients receiving postoperative chemotherapy alone, and patients receiving neither peritonectomy nor postoperative chemotherapy (27.33 vs 12.00 vs 16.00 vs 10.33 months, p  < 0.001). In the multivariate analysis, poor performance status ( p  = 0.036), absence of complete gross peritonectomy ( p  < 0.001), and lack of postoperative chemotherapy ( p  < 0.001) were identified as independently associated with poor survival. The data indicate complete gross peritonectomy following gastrectomy confers a survival benefit to gastric cancer patients with intraoperatively proven single P1/P2 carcinomatosis. In addition, postoperative chemotherapy improves survival regardless of resection of peritoneal carcinomatosis and should be recommended.